2008
DOI: 10.1186/1471-2121-9-41
|View full text |Cite
|
Sign up to set email alerts
|

New steroidal aromatase inhibitors: Suppression of estrogen-dependent breast cancer cell proliferation and induction of cell death

Abstract: BackgroundAromatase, the cytochrome P-450 enzyme (CYP19) responsible for estrogen biosynthesis, is an important target for the treatment of estrogen-dependent breast cancer. In fact, the use of synthetic aromatase inhibitors (AI), which induce suppression of estrogen synthesis, has shown to be an effective alternative to the classical tamoxifen for the treatment of postmenopausal patients with ER-positive breast cancer. New AIs obtained, in our laboratory, by modification of the A and D-rings of the natural su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…It has also been reported that some AIs, like letrozole, anastrozole and formestane inhibit proliferation of breast cancer cells by inducing cell cycle arrest in G 0 /G 1 phase and cell death by apoptosis [13], [23]. Recently, we demonstrated that the steroidal AIs 5α-androst-3-en-17-one and 3α,4α-epoxy-5α-androstan-17-one, previously synthesized in our laboratory [24], inhibit cell proliferation in various tumour cell lines [25] and induce apoptosis and autophagy in MCF-7aro cell line [26]. Nevertheless, the effects of exemestane in breast cancer cells are not totally understood.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been reported that some AIs, like letrozole, anastrozole and formestane inhibit proliferation of breast cancer cells by inducing cell cycle arrest in G 0 /G 1 phase and cell death by apoptosis [13], [23]. Recently, we demonstrated that the steroidal AIs 5α-androst-3-en-17-one and 3α,4α-epoxy-5α-androstan-17-one, previously synthesized in our laboratory [24], inhibit cell proliferation in various tumour cell lines [25] and induce apoptosis and autophagy in MCF-7aro cell line [26]. Nevertheless, the effects of exemestane in breast cancer cells are not totally understood.…”
Section: Introductionmentioning
confidence: 99%
“…Protein glycosylation represents one of the most common but complex post-translational protein modifications (Walsh and Jefferis, 2006) and has hitherto only been described for CYP19A1 (Cepa et al, 2008) among the human P450 enzymes. Because microsomal forms of P450 are oriented toward the cytoplasm, it is evident that they cannot be exposed to the glycosylation machinery residing in the luminal compartment of the ER.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, testosterone and its non-aromatizable metabolite 5a-dihydrotestosterone (DHT), the most potent natural ligand for the AR (K D 10 -11 mol/L compared with 10 -9 mol/L for testosterone and 2=10 -7 mol/L for androstenedione), inhibit MCF-7 growth and E 2 -mediated upregulation of PR protein expression, presumably via AR signaling (32)(33)(34). Because MCF-7aro breast cancer cell line expresses high aromatase activity, it was observed that testosterone (1 nmol/L) can also stimulate MCF-7aro cell growth and that anti-aromatases have the ability to inhibit this proliferative effect, which indicates that the aromatization of testosterone with production of E 2 was responsible for the androgen-mediated cell growth (35,36). Compared with testosterone, androstenedione only slightly stimulates MCF-7 cell growth.…”
Section: Discussionmentioning
confidence: 97%